DEKONSTRUKSI EFEKTIVITAS ZAKAT DAN WAKAF DALAM PENGENTASAN KEMISKINAN DI INDONESIA DAN MALAYSIA: SEBUAH TINJAUAN KRITIS DAN ANALISIS STRUKTURAL - Muhammad Roihan Qowima; Yaumi Nurul Khamisa; Citra Adisty Perdana; Asyifa Meidy Fadhilah; Nailah Zahrotun Ni’mah; Wijdan Kusumawardani; Muhammad Fachri Aditya; Normalasari Normalasari; Quranique Qurrota Aini; Valika Ainindiya Maylaffaiza Rohana; Della Amelia; Alfi Syah; Fauzi Fauzi (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The narrative of zakat and waqf as key instruments for poverty alleviation is often utopian and ignores structural realities. This article deconstructs the effectiveness of zakat and waqf in Indonesia and Malaysia by highlighting the gap between theoretical potential and actual realization. Using the Systematic Literature Review (SLR) method and the latest statistical data analysis (2020–2025), the study found that the contribution of zakat to the reduction of the national poverty rate in Indonesia only ranges from 1.44% to 2.28%. The main failures are recorded in institutional inefficiencies, as seen in the low Allocation to Collection Ratio (ACR), a crisis of public trust in management, and the phenomenon of “idle land” in waqf assets that accumulate without productivity. The practical impact shows that zakat and waqf interventions are often palliative, providing temporary assistance that does not break the mechanism of poverty reproduction, and risk perpetuating dependency (dependency trap) for mustahik. This article asserts that without radical managerial reform, increased accountability, transparency, and strategies for the productive use of waqf assets, both instruments will remain far from their redistributive potential. Policy recommendations are directed at management reform, data integration, and socio-economic investment models to achieve more substantive impact. The study also encourages cross-sector coordination, capacity building for managers, evidence-based monitoring and evaluation mechanisms, and legal framework updates as prerequisites for realizing the distributive potential of zakat and waqf as well as pro-inclusive national fiscal policies.